EXPERIENCES OF FOREIGN POSTS APPLYING FRANCHISING - Vopalecka, Barbara (Doprava a spoje, 2010)
Franchising is one of effective possibilities of developing a company and facing its competitors while keeping costs under control. Many foreign posts such as Swiss Post or Deutsche Post have large, long-term and positive experience with applying franchising in their postal business. Czech Post works on introducing this product sales form into practice at present.